2005
DOI: 10.1111/j.1475-4762.2005.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion, universal banking and post offices in Britain

Abstract: The causes and consequences of financial exclusion have become a policy concern in Britain in recent years. This paper analyses policy discourses around financial exclusion and considers the (social and economic) geographical issues surrounding one particular policy response – universal banking services. It examines the policy background which led to the introduction of these services, and the institutional role of the Post Office, before discussing their potential social and spatial consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 8 publications
(8 reference statements)
0
30
1
Order By: Relevance
“…Similarly, analysis of the relationship between inclusion policies and financial exclusion revealed that, when costly inclusion policies are implemented, the higher costs are transferred to customers, limiting their access to financial services and collect money at low costs. Use of this programme in the UK is especially not eworthy (Fuller & Mellor, 2008;McKillop et al, 2007;Midgley, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, analysis of the relationship between inclusion policies and financial exclusion revealed that, when costly inclusion policies are implemented, the higher costs are transferred to customers, limiting their access to financial services and collect money at low costs. Use of this programme in the UK is especially not eworthy (Fuller & Mellor, 2008;McKillop et al, 2007;Midgley, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Financial inclusion originated as a solution to the exclusion of individuals from the banking system using technology for online banking or agents that facilitate financial sector coverage. The fact that individuals excluded as a result of banks' preference for those clients with profitable income over the ones perceived as 'low-income' drives banks to engage exclusively with clients who are regarded as offering financial institutions profit opportunities (Midgley, 2005). Financial inclusion can be understood as the creation of financial sector policies that compel the creation of programmes to make banking services accessible to all (Bernad, Fuentelsaz & Gómez, 2008;Marshall, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the logic of the argument presented by the BBA seemed to be that the provision of additional distribution channels was conditional upon the closure of branches. Fortunately for the banking industry, the BBA's conclusions converged with those of PAT 14, perhaps unsurprising given that the latter's analysis of the problem appears to be largely reliant on these two very same BBA reports, reports which were researched and written by one of the members of the Policy Action Team (Kempson), and the Government's own reluctance to legislate, its insistence on “market solutions” and its desire to modernise the Post Office and automate welfare payments (Midgley 2005).…”
Section: A Policy History Of Branch Closurementioning
confidence: 94%
“…If basic bank accounts were developed as a solution to the structural problems of access to financial services, the enrolment of the Post Office through the development of universal banking services was explicitly designed as a solution to the problem of geographical access and of branch closure. As Midgley (2005) has stressed, there were two reasons for the enrolment of the Post Office. First, the sheer spatial “reach” of the Post Office network, which possessed a “branch network that in 1999, when universal banking was in development, stood at around 18,400 offices in the UK” (Midgley 2005:279).…”
Section: A Policy History Of Branch Closurementioning
confidence: 99%
“…BBAs and POCAs to some extent reflected the government's opinion that the financially excluded are legitimately excluded by providers, given their higher risk profiles, meaning that less risky (although less functional) products will encourage providers to offer a more limited or 'particularistic' form of financial inclusion (Midgeley, 2005 'asset-based welfare', which he defines as a turn 'away from the passive receipt of stateprovided welfare services and towards active management of assets through which individuals become personally responsible for releasing future income streams when welfare needs demand they do so' (Watson, 2009: 42).…”
Section: Financial Inclusion and Welfare Provisionmentioning
confidence: 99%